2022
DOI: 10.5194/gmd-15-8785-2022
|View full text |Cite
|
Sign up to set email alerts
|

Basin-scale gyres and mesoscale eddies in large lakes: a novel procedure for their detection and characterization, assessed in Lake Geneva

Abstract: Abstract. In large lakes subject to the Coriolis force, basin-scale gyres and mesoscale eddies, i.e. rotating coherent water masses, play a key role in spreading biochemical materials and energy throughout the lake. In order to assess the spatial and temporal extent of gyres and eddies, their dynamics and vertical structure, as well as to validate their prediction in numerical simulation results, detailed transect field observations are needed. However, at present it is difficult to forecast when and where suc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 78 publications
0
24
0
Order By: Relevance
“…This study focuses on Bise wind events that caused the formation of a cyclonic gyre and pelagic upwelling in the central region of the Grand Lac basin of Lake Geneva. This gyre is part of a three‐gyre pattern that was previously identified as the typical response to strong Bise winds blowing over lake (Hamze‐Ziabari, Lemmin, et al., 2022; Figure 1c). Pelagic upwelling is important for the ecological development of the lake, since it transports nutrients from the deeper layers into the phototrophic zone.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…This study focuses on Bise wind events that caused the formation of a cyclonic gyre and pelagic upwelling in the central region of the Grand Lac basin of Lake Geneva. This gyre is part of a three‐gyre pattern that was previously identified as the typical response to strong Bise winds blowing over lake (Hamze‐Ziabari, Lemmin, et al., 2022; Figure 1c). Pelagic upwelling is important for the ecological development of the lake, since it transports nutrients from the deeper layers into the phototrophic zone.…”
Section: Resultsmentioning
confidence: 62%
“…(2022), Hamze‐Ziabri, Fouroughan, et al., 2022), Hamze‐Ziabari, Lemmin, et al. (2022), Hamze‐Ziabri, Razmi, et al. (2022), and Reiss et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2019) showed that wind‐induced coastal downwelling can also transport coastal water downslope to ∼200‐m depth, thus contributing to the renewal of intermediate hypolimnion layers. Ever present basin‐scale gyres and mesoscale eddies (Hamze‐Ziabari, Lemmin, et al., 2022) spread these advected water masses in the intermediate hypolimnion layers throughout the basin. However, these processes do not reach the deepest layer (∼300‐m depth) of the Grand Lac .…”
Section: Introductionmentioning
confidence: 99%